Two Coarse Spatial Patterns of Altered Brain Microstructure Predict Post-traumatic Amnesia in the Subacute Stage of Severe Traumatic Brain Injury - Andreasen, Sara H.; Andersen, Kasper W.; Conde, Virginia; Dyrby, Tim B.; Puonti, Oula; Kammersgaard, Lars P.; Madsen, Camilla G.; Madsen, Kristoffer H.; Poulsen, Ingrid; Siebner, Hartwig R. (Frontiers in Neurology, 2020)
Severe traumatic brain injury (TBI) causes diffuse damage to neural axons in the deep white matter regions of the brain. Diffuse axonal injury results in alteration in regional water diffusion that can be mapped with diffusion tensor imaging (DTI) of the brain´s microstructure. Here we show in 14 severely injured TBI patients that whole-brain DTI of microstructural injury, performed in the subacute stage, can predict the duration of memory impairment after TBI, called posttraumatic amnesia. Using coarse parcellation of the brain in five regions, we identified two spatial pattern that predicted post-traumatic amnesia. Both, the amount of diffuse microstructural changes affecting all five brain regions and preferential damage of central brain structures predicted the individual duration of memory impairment. Our preliminary data in a small group of well-characterized patients suggest that a coarse spatial analysis of diffuse brain damage with DTI has potential to assist individual prognostication after severe TBI.